Civil-legal consequences of the technical measures of copyright protection elimination under Russian law - Kirsanov, Alexey N.; Popovich, Alexey A. (Journal of the Belarusian State University. Law, 2023)
The issues of the application of civil liability measures resulting from the elimination (circumvention) of technical measures of copyright protection in accordance with the current provisions of the Russian civil law are analysed. The article considers the legal nature of compensation as a measure of civil liability for violation of exclusive rights. Based on the analysis of judicial practice, the features of the application of compensation as a measure of civil liability, as well as the fundamental differences between the recovery of compensation from damages, are revealed. Taking into account the legal regulation specifics of technical measures of copyright protection, cases of possible application of civil liability measures that are not directly provided for by the provisions of the law regulating the use of technical measures of copyright protection by copyright holders are considered in detail. It is proposed to expand the list of liability measures applied to violators who eliminate technical measures of protection, as well as to expand the range of subjects who have the right to appeal to the court with requirements for the application of civil liability measures against the actions of persons aimed at eliminating technical measures of copyright protection.
Keywords: copyright; compensation; damages; technical measures of copyright protection; liability for copyright infringement; intellectual property law; civil law